المؤسسات العامة في المدينة الإسلامية - احمد حسين أريج; غالب عباس هديل (Journal of College of Education, 2021)
The public establishments in the Islamic city have varied and varied, some of which were religious purposes, some of which were civil ones, and these facilities varied from one era to another, and from one city to another to meet the collective needs of the people. In establishing them, and endowing them, and endowments for endowments, so that the public can benefit from them and achieve the purpose of their establishment. Public institutions are an important aspect of life in the Islamic city, such as mosques, schools, libraries, and other institutions and their various facilities. Therefore, my research has been divided into two chapters. The first topic talks about religious institutions that include mosques, scholars’ homes, and mystic facilities. The second study talks about educational institutions that include Schools, libraries, bookcases and city lighting